Administration of statins is correlated with favourable prognosis in lung cancer patients receiving immune checkpoint inhibitors - Yang, Jingjing; Lin, Jie; Guo, Huaijuan; Wu, Wenjuan; Wang, Jiaxin; Mao, Jingxian; Fan, Wenbin; Lu, Yang; Wang, Ying; Yan, Xuebing (Frontiers in Immunology, 2025)
ObjectiveStatins are commonly used for cardiovascular diseases and recent studies have supported their anti-cancer role in numerous human malignancies. This study aims to investigate their prognostic impact in lung cancer patients receiving immune checkpoint inhibitors (ICIs).MethodsA retrospective analysis was performed based on the clinical data from 235 lung cancer patients who received ICI therapy between 2019 and 2024 in three hospitals. The correlation of statin use with overall survival (OS) or progression-free survival (PFS) was analyzed. Then, a comprehensive bioinformatics analysis was used to identify prognostic target genes of statins and investigate their correlation with immune infiltration, followed by validation in an independent cohort and cellular experiments.ResultsIn the whole cohort, 80 patients (34.0%) received statins. The statin users had a significantly better OS and PFS than the non-statin users. Statin use was an independent favorable prognostic factor for ICI-treated lung cancer patients. Transcription factor RAR-related orphan receptor alpha (RORA) was identified as a favorable prognostic target gene of statins. RORA was found to be downregulated in lung cancer tissues and correlated with infiltration of some immune cells. In the validation cohort, RORA expression was positively correlated with CD8+ T cell infiltration in lung cancer tissues, and improved prognosis in lung cancer patients receiving ICIs. Atorvastatin treatment increased RORA expression and RORA knockdown partly antagonized the inhibitory role of Atorvastatin on the malignant characteristics of lung cancer cells in vitro.ConclusionStatin use was significantly correlated with improved prognosis in lung cancer patients receiving ICIs. Statins may enhance ICI efficacy partly through RORA. Due to study limitations, the actual role of statins and their target genes in anti-cancer immunity needs further investigations.